(3cJGH gQeS GdLGeY ddCTjGAs - (3HdjfGS GdMcjes
(3ChdgG (B:s
(3hceG bdJ(B: (3Ydi GdCLSGO GdUe GdehGJ GdJi gi eJYdbI HJUQja GdCReGf hMQcGJ GdCadGc hJZjjQ GdHdGO hGdHbGY hGdCeGcf YfO EJUGd GdZdjX HGdZdjX s
(3BNQgG (B:s
(3hGJUd cd Tcd HTcdg jchf ef dWjagG bdH GdTLQ, hjOaY GdZdjX Edi NGQLg dbdI EJUGdg, aEPG CUGHg HQO GdghGA aUGQ bThQkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B119 - (3U(B124s
(3GfXQg eY GdQTO Qbe (B" 730"s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs